POTENSI KEARIFAN LOKAL SUKU MANDAR DALAM MEMPERKUAT KARAKTER CINTA TANAH AIR PESERTA DIDIK SEKOLAH DASAR - Eva Veriani; Eko Handoyo; Hanafi Hussin; Eko Armaidi (STKIP Subang, 2026)
The weakening of the patriotic character of elementary school students due to the influence of globalization, foreign cultures, and the development of digital technology causes students to tend to be less familiar with their own local culture, so it is important to examine how the local wisdom of the Mandar Tribe can strengthen the patriotic character of elementary school students. The study used a qualitative descriptive method with a library research approach. Data were obtained through various literature sources in the form of scientific articles, journals, books, and documents relevant to character education, local wisdom, Mandar culture, and nationalism. The findings of this study indicate that the local wisdom of the Mandar Tribe has values ​​relevant to strengthening the patriotic character, such as Metawe (mutual respect), Siwaliparri (mutual cooperation), Metabe (mutual assistance), and Mepuang (hospitality). These values ​​can be integrated into learning through subjects, extracurricular activities, and habits at school. Integrating the local wisdom of the Mandar people not only helps preserve regional culture but also builds national identity, encourages pride in the country's culture, and forms the character of students who are responsible, tolerant, and empathetic. Therefore, the local knowledge of the Mandar people can function as a strategic and contextual learning tool to help elementary school students develop a stronger sense of love for their homeland.